2020
DOI: 10.3389/fphar.2020.01138
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Selenocysteine as a Potential Nanomedicine Promotes Cartilage Regeneration With Enhanced Immune Response by Text Mining and Biomedical Databases

Abstract: Meanwhile, these genes were mainly associated with immune response, immune mediator induction, and cell chemotaxis. Significant support is provided for obtaining a series of novel gene targets, and we identify potential mechanisms for cartilage regeneration and final nanomedicine immunotherapy in regenerative medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Here we have shown the mechanisms behind trafficking of SLC38A6 in the glutamate–glutamine cycle in neuronal cells. The trafficking mechanisms could be functioning in other cell types where SLC38A6 expression is found which includes pancreas [ 39 ], cartilage [ 40 ], circulatory tissue [ 41 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…Here we have shown the mechanisms behind trafficking of SLC38A6 in the glutamate–glutamine cycle in neuronal cells. The trafficking mechanisms could be functioning in other cell types where SLC38A6 expression is found which includes pancreas [ 39 ], cartilage [ 40 ], circulatory tissue [ 41 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the tumor promotion effect of FAM20A may be accomplished through the activation of FAM20C. A recent study showed that FAM20A can be used as a prospective biomarker for the diagnosis and biomaterial drug therapy of cartilage lesions ( 83 ). FAM20A is involved in cartilage regeneration and mainly related to immune response and cell chemotaxis, thus can be used as the final nanomedicine immunotherapy in regenerative medicine ( 83 ).…”
Section: The Role Of the Secretory Pathway Kinases Or Kinase-like Pro...mentioning
confidence: 99%
“…Moreover, findings of a microarray analysis have revealed that medroxyprogesterone acetate (MPA), a progestin-based hormonal contraceptive designed to mimic progesterone, increases expression of genes related to inflammation and cholesterol synthesis, as well as those genes associated with both innate immunity and HIV-1 susceptibility [160]. Finally, integrative microarray data have been exploited to identify eight hub genes and one potential nanomedicinal drug, Selenocysteine, that promotes cartilage regeneration [161].…”
Section: Microarrays and Drug Discovery For Various Other Pathologiesmentioning
confidence: 99%